Body on the Plate. On the Relation between the Carnality and Food (on the example of meat in advertising) - Goszczyński, Wojciech; Wójtewicz, Anna (Qualitative Sociology Review, 2018)
Do we own our bodies? Do we control them during the meal, or does the meal control us? In this paper, we aim to examine the complex nexus of social and physical practices embedded in eating habits. During the examination of selected culinary advertisements, we will attempt to explain how food stabilizes, catalyzes, separates, and mediates social relations, as well as social and individual bodies. The paper merges the perspective of cultural anthropology, sociology of the body, and food studies.